Synthesis of 1,4-dihydropyrimidines with immobilized urease: Effect of method immobilization on magnetic supports - Vargas, Annie Y. (2017)
The effect of the urease immobilization method was studied on magnetic supports for the Biginelli/Hantzsch reaction. For this purpose, Fe3O4/SiO2 was modified with 3-Aminopropyl-Triethoxysilane and then activated with glutaraldehyde. A ratio of 500 mg of enzyme per gram of support at 4°C and 18 h were sufficient for the physical adsorption, while 24 h were required for covalent bonding. The Biginelli and Hantzsch reactions were used to evaluate urease application in multicomponent reactions (MCRs). The synthesis of 1,4-dihydropyrimidines was successfully performed using immobilized urease favoring the Hantzsch product. The magnetic properties of the supports allow easy separation, and the urease immobilized by both methods improved the enzymatic activity compared to that of free urease.